Effects of adolescent onset voluntary drinking followed by ethanol vapor exposure on subsequent ethanol consumption during protracted withdrawal in adult Wistar rats - Criado, Jose R. (2012)
Epidemiological studies have demonstrated that heavy drinking and alcohol abuse and dependence peak during the transition between late adolescence and early adulthood. The objective of the present study was to determine whether a model of early onset adolescent ethanol drinking exposure that is followed by an ethanol vapor regimen during late adolescence and young adulthood leads to an increase in drinking in adulthood. In this model, initiation of voluntary ethanol drinking in adolescence, using a sweetened solution, was followed by an 8-wk intermittent ethanol vapor regimen in Wistar rats. A limited-access two-bottle choice paradigm was then used to measure intake of a 10% (w/v) ethanol solution. No differences in water intake (g/kg), total fluid intake (ml/kg) and body weight (g) were observed between air-exposed and ethanol-vapor exposed groups during the pre-vapor and post-vapor phases. The eight wks of ethanol vapor exposure was found to produce only a modest, but statistically significant, elevation of ethanol intake during the protracted withdrawal period, compared to air-exposed rats. A significant increase in ethanol preference ratio was also observed in ethanol-vapor exposed rats during the sucrose-fading phase, but not during the protracted withdrawal period. The findings from the present study suggest that in addition to alcohol exposure, environmental variables that impact appetitive as well as consumptive behaviors may be important in developing robust drinking effects that model, in animals, the increased risk for alcohol dependence seen in some human adolescents who begin drinking at an early age.